Femtoliter tunable optical cavity arrays. - Dolan, P; Hughes, G; Grazioso, F; Patton, B; Smith, J (2010)
Large arrays of uniform, precisely tunable, open-access optical microcavities with mode volumes as small as 2.2 μm(3) are reported. The cavities show clear Hermite-Gauss mode structure and display finesses up to 460, in addition to quality (Q) factors in excess of 10,000. The cavities are attractive for use in quantum optics applications, such as single atom detection and efficient single photon sources, and have potential to be extended for experiments in the strong coupling regime.